Encyclopaedia of physical education and sports Vol.3 An introduction to supervision in physical education and sport - Sharma, Bela Rani (ed); Mudgal, Rahul (Ed); Kaushik, Vijaya (Ed.) (New Delhi Sarup Book Publishers, 2012)
Concept of supervision